2015
DOI: 10.1152/ajpregu.00154.2015
|View full text |Cite
|
Sign up to set email alerts
|

An increased population of regulatory T cells improves the pathophysiology of placental ischemia in a rat model of preeclampsia

Abstract: The reduced uterine perfusion pressure (RUPP) rat model of preeclampsia exhibits much of the pathology characterizing this disease, such as hypertension, inflammation, suppressed regulatory T cells (T Regs), reactive oxygen species (ROS), and autoantibodies to the ANG II type I receptor (AT1-AA) during pregnancy. The objective of this study was to determine whether supplementation of normal pregnant (NP) TRegs into RUPP rats would attenuate the pathophysiology associated with preeclampsia during pregnancy. CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 46 publications
6
69
1
Order By: Relevance
“…Adoptive transfer studies have confirmed that CD4ϩ T-cell function in RUPP rats is altered to promote the production of AT 1 -AA, ET-1, and sFlt-1 in otherwise healthy pregnant rats, as mechanisms of increasing blood pressure during pregnancy (12,49,50). CD4ϩ T-cell population was increased in RUPP compared with NP rats, and TREGs were decreased, consistent with what has been published previously (3,11,14,49,63). Data in the literature have shown that VD reduces proinflammatory CD4ϩ T cells and increases proliferation of TREGs in nonpregnant animals (10,29,31,39).…”
Section: R350 Vit D Improves Pathophysiology In Preeclamptic Rat Modelsupporting
confidence: 86%
“…Adoptive transfer studies have confirmed that CD4ϩ T-cell function in RUPP rats is altered to promote the production of AT 1 -AA, ET-1, and sFlt-1 in otherwise healthy pregnant rats, as mechanisms of increasing blood pressure during pregnancy (12,49,50). CD4ϩ T-cell population was increased in RUPP compared with NP rats, and TREGs were decreased, consistent with what has been published previously (3,11,14,49,63). Data in the literature have shown that VD reduces proinflammatory CD4ϩ T cells and increases proliferation of TREGs in nonpregnant animals (10,29,31,39).…”
Section: R350 Vit D Improves Pathophysiology In Preeclamptic Rat Modelsupporting
confidence: 86%
“…Previous in vitro and in vivo experimental studies have indicated that IL-10 expression may influence preeclampsia pathogenesis (Medeiros et al, 2014;Cornelius et al, 2015;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…LIGHT, a TNF superfamily member, is also increased in PE and may contribute to placental damage and ischemia (Wang et al, 2014). Plasma levels and CD4 + T cell production of TNF-α are increased in RUPP compared with Norm-Preg rats (LaMarca et al, 2008a; Wallace et al, 2011; Cornelius et al, 2015). Infusion of TNF-α causes HTN and proteinuria during late pregnancy in baboons (Sunderland et al, 2011), rats (Alexander et al, 2002) and mice (Bobek et al, 2015) (Table 5).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 94%
“…In RUPP rats, the levels of sEng increase in both serum and placenta (Gilbert et al, 2009) while serum TGF-β levels decrease (Cornelius et al, 2015) (Table 4). However, no changes in sEng levels were observed in rat models of HTN-Preg produced by DOCA-salt or L-NAME (Agunanne et al, 2010; Ramesar et al, 2011) (Table 5).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation